2020
DOI: 10.4102/koedoe.v62i1.1631
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Environmental Impact Assessment report quality in South African national parks

Abstract: Conservation implications:The results show that EIA reports for developments in South African national parks are generally of sufficient quality for decision-making that benefits conservation. However, weaker performance regarding waste, significance determination, water-related impacts and a lack of consideration of strategic context requires a conservation-specific EIA report quality review package to improve report quality in the areas of weakness and thereby increase the value of EIA as an instrument for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Only some of the cases reviewed provided clear statements on the cumulative impacts associated with the particular project. The above aligns with previous research in the international and South African context, that found dealing with significance remains a key challenge (Arts et al 2012;Ehrlich and Ross 2015;Retief, et al 2016;Sandham et al 2020;Alberts et al 2021a)…”
Section: Significancesupporting
confidence: 88%
See 2 more Smart Citations
“…Only some of the cases reviewed provided clear statements on the cumulative impacts associated with the particular project. The above aligns with previous research in the international and South African context, that found dealing with significance remains a key challenge (Arts et al 2012;Ehrlich and Ross 2015;Retief, et al 2016;Sandham et al 2020;Alberts et al 2021a)…”
Section: Significancesupporting
confidence: 88%
“…A distinction can however be made between 'administratively correct' EIA decisions and 'good' EIA decisions (Alberts et al 2021b) KPIs were chosen that are empirically measurable and for which data could be obtained from EIA case files. The KPIs addressed South African minimum legal requirements and international best practice for EIA report substance, based on an adapted and contextualised Lee and Colley method (Adapted from Alberts et al, 2020;Alberts et al 2021a;Sandham et al 2008aSandham et al , 2020 -see Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is conceivable that you have a just (correct) but poor decision. Based on what other authors have found when looking at EIA outcomes and substance (Sadler 1996;Wood 2003;Morgan 2012;Jones and Fischer 2016;Sandham et al 2020), we suspect that this might be happening regularly. An important question arising is then to what extent poor substance is being incorporated into just or administratively correct EIA decisions?…”
Section: Conclusion and Recommendationsmentioning
confidence: 65%
“…Secondly, the EIA system is also well researched with a meaningful body of evaluation literature (see for example Retief 2010;Retief, Fischer, et al 2020;Hallat, Retief, and Sandham 2015;Sandham, Moloto, and Retief 2008;Sandham, Hoffman, and Retief 2008;Sandham, Carrol, and Retief 2010;Sandham et al 2013;Sandham, Van der Vyver, and Retief 2013;Sandham et al 2020;Kidd, Retief, and Alberts 2018;Swanepoel et al 2019). Finally, administrative justice in South Africa is a wellentrenched legal principle, with a specific constitutional right (in Section 33 of the Constitution of the Republic of South Africa) as well as national legislation protecting this right to just administrative action (Kotz e 2004;Kidd, Retief, and Alberts 2018).…”
mentioning
confidence: 99%